Makna Religiusitas pada Orang dengan HIV/AIDS di Banda Aceh - Safrilsyah Safrilsyah; Rena Irmayani; Nurafni Nurafni (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2016)
This study aims to understanding the spirituality meaning on HIV/AIDS Survivor. Subjects in this study is 1 HIV/AIDS survivors at the age of 15-30 years old. This study is a qualitative study. Data obtained by interview and observation. Results of this study show that religiousity has an influence to survivor’s acceptance. When subjects were diagnosed by the doctor, they felt depressed and unstable. They even thought that God is unfair. But after one or two months, some of the subject became more religious. They thought that the religion’s ritual had a good effect for their mental and spiritual health.